INSEMINASI NILAI-NILAI ISLAM DALAM PELAJARAN EKONOMI DI MADRASAH ALIYAH NEGERI YOGYAKARTA III - Junanah, Junanah; Yulianti, Rahmani Timorita; Yusdani, Yusdani (Pusat Penelitian dan Pengabdian Masyarakat (P3M) STAIN Jurai Siwo Metro, 2015)
This article is the result of research that aims to describe the Islamic values in economic subjects in MAN Yogyakarta III. In addition, based on the findings of this research used as a basis for designing modules economic subjects charged Islamic values as a guide teachers to teach economics at MAN Yogyakarta III. Subjects in this study was the deputy head of the curriculum MAN Yogyakarta III, MAN Yogyakarta III economics teacher, and several students majoring in social studies MAN Yogyakarta III. Selection of subjects in this study was porpusive sampling. Primary data were collected through interviews and secondary data supported by relevant documents. The data were analyzed using descriptive qualitative method by steps: data collection, data reduction, data display and analysis. The results of this study has been indicated that the economic subjects in MAN Yogyakarta III still tend to be dominated values-liberal capitalist economy, while Islamic economics or economics based on Islamic values have not taught formally. As for the design of the modules loaded Islamic values in economic subjects in MAN Yogyakarta III proposed consists of three stages, namely; analysis, design, and development.KeywordsÂ : Economics subject, Islamic value, insemination, State Islamic Senior High Scool III of Yogyakarta